Peningkatan Kompetensi Guru TK sebagai Inovasi Pembelajaran melalui Pelatihan Canva: Increasing Kindergarten Teacher Competency as a Learning Innovation through Canva Training - Wisudawati, Nidya; Hastarina, Merisha; Damayanti, Nadia Eka; Syahdilla, Syahdilla (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Mutiara Islami Kindergarten is an early childhood school on Jalan Kadir TKR Palembang. Based on the results of observations, the teaching and learning process in kindergarten schools is quite different from that in elementary schools, and the school hours are relatively short, from 08.00 to 10.00 WIB, with the average age of students being 4 to 6 years. Kindergarten teachers must be required to be more creative in mediating learning materials so that they are effective and appropriate. Teachers must use learning media that include audio, visual, and audiovisual aspects, as these three aspects are not achieved when limited to books. One way to maximize Information and Communication Technology (ICT) use is through the Canva application. This application is expected to make the work of kindergarten teachers easier, increase children's interest and enjoyment, and increase confidence in learning.